Evaluation of the Edinburgh police research and practice group - Young, Suzanne (Report, 2012)
In association with the Scottish Institute for Policing Research (SIPR), the Edinburgh Police Research and Practice Group (EPRPG) is an SCCJR knowledge transfer project funded by the Arts and Humanities Research Council (AHRC) established to facilitate research-oriented collaboration between police practitioners, policy makers and academics. The project activities included a series of seminars and workshops to disseminate research evidence to frontline practitioners, and to engage in collaborative thinking about research priorities. The Edinburgh Police Research and Practice Group was funded by the Arts and Humanities Research Council (AHRC), under its knowledge transfer scheme.